Zmiany w konstrukcji podatku dochodowego od osób fizycznych jako element długoterminowej polityki podatkowej - Gasz, Małgorzata (Changes in the structure of personal income tax as a component of long-term taxation policy, 2006)
The objective of this article is to present an analysis of changes in selected structural elements of personal income tax that have been introduced from the time the tax first appeared in the modem Polish lax system until now. Prerequisites for introducing changes in individual tax structures may be quite varied and include e.g. reaching some definite objective of internal policy (reduction of budgetary deficit) or improving the international position of a given country. Such objectives are easier to achieve with a system based on efficient and easily executable taxes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 180-187